DETERMINASI TINGKAT KEMANDIRIAN FISKAL 62 KABUPATEN TERTINGGAL DI INDONESIA - Nurhayati; Sri Yani Kusumastuti; Nur Hidayatullah; Agustina Suparyati (Media Ekonomi, 2022)
This study aims to see the determination of regional fiskal independence in 62 underdeveloped districts in Indonesia. This research data was obtained from secondary with a sample of 62 underdeveloped districts in Indonesia from the period 2014-2019. This research uses a Multiple Linear Regression analysis tool with panel data. The test results show that those that have a sign that is in accordance with expectations and statistically significant are economic growth and local revenue with an error rate of 5%, then H1 and H3 are accepted. While the poverty rate has no effect on the fiscal independence of 62 underdeveloped districts in Indonesia, H2 is rejected. The results of this study are expected to contribute to research on regional development and sustainable development in Indonesia, especially for studies on how to reduce the backwardness of districts in Indonesia.